Answer:
Step-by-step explanation:
Given a circle centre J
Let the radius of the circle =r
LK is tangent to circle J at point K
From the diagram attached
Theorem: The angle between a tangent and a radius is 90 degrees.
By the theorem above, Triangle JLK forms a right triangle with LJ as the hypotenuse.
Using Pythagoras Theorem:
The length of the radius,
2 to the 12th power should be correct
Answer:
x^2 - 2x - 4
Step-by-step explanation:
g(x) - f(x) = (x^2 + 1) - (2x + 5) = x^2 + 1 - 2x -5 = x^2 -2x +(1-5) = x^2 - 2x - 4
Answer:
Step-by-step explanation: Let x be the smaller and y be the largest number.
Since x+y=13, we deduce y=13-x
Now, for the translation: "two more than the larger number" is y+2 , while "twice the smaller" is 2x
Their sum is y+2+2x
And since we know that y=13-x, we have y+2+2x=13-x+2+2=15+x